Algebraic Thinking Ability Based on Mathematics Disposition in Learning Cycle 7E Model - Rahmawati, Anis; Kartono, Kartono; Hidayah, Isti (Unnes Journal of Mathematics Education Research, 2019)
The aim of this study are to determine the quality of the Learning Cycle 7E model and found a pattern of algebraic thinking ability of 7th grade students’ in solving algebra problem viewed by disposition mathematics. The research uses mixed methods study with concurrent embeded design. The subjects of this research were 7th grade students. Quantitative data was tested with the z test and Independent t-test, whereas qualitative data were analyzed descriptively. Learning quality is assessed from the planning, implementation and evaluation stage. The result of this research shows that Learning Cycle 7E model in good criteria. Students in the high mathematical disposition category were able to solve the algebraic problem from the generalization level, the transformational level until the meta-global level. Students in the medium mathematical disposition category were able to solve the algebraic problem from the generalization level and the transformational level. And students in the low mathematical disposition category were able to solve the algebraic problem only at the the generalization level.